Assessment center perspectives for talent management strategies - Thornton, George C. (New York Routledge, 2015)
Written by three leading scholars with vast experience in the science and practice of assessment centers (ACs), this is the first volume to comprehensively integrate variations of the assessment center method with alternative talent management strategies. A useful reference guide, it examines the many ways in which organizations can apply the assessment center method to achieve their talent management goals. It provides balanced and in-depth coverage of theory, research, and practice pertaining to the dimension-, task-, and multifaceted-perspectives on the AC method. Ideal for researchers, practitioners, and students alike, and well suited for courses in testing and measurement, personnel selection, HR planning and staffing, training and development, and organizational change, Assessment Center Perspectives for Talent Management Strategies is a complete and up-to-date account of the assessment center method.
Includes bibliographical references and index.
Keywords: Assessment centers (Personnel management procedure)